Effect of eggshell and lime on growth and mineral nutrition of kalmi (Ipomoea aquatica: Convolvulaceae) grown on lead contaminated soil (Journal of Biodiversity Conservation and Bioresource Management, 2019)
A pot experiment was conducted to evaluate the effect of Eggshell and Lime in ameliorating lead uptake to alleviate toxicity of lead in Kalmi (Ipomoea aquatica).The lengths, fresh and dry weights of shoot was decreased significantly in 200 mg Pb kg-1soil as compared to the control. The similar significant decreasing trend in macro nutrient concentration in shoot and root was also observed. The percentage of N, P, K, S, Mg and Ca concentrations in edible parts (shoots) decreased by 7.73, 54.55, 12.50, 35.29, 17.65 and 19.61, respectively in 200 mg Pb kg-1 treated pots compared to the control. On the other hand, Pb concentration in shoot and root was the highest at 200 mg Pb kg-1 treated pots (36.14 and 111.14 mg Pb kg-1) and the lowest was in the control treatment (3.48 and 14.48 mg Pb kg-1 pot-1). Treatments of lime and eggshell had positive effects on the productivity of Kalmi and remediating the effect of lead uptake by the plants. Between the two amendments eggshell showed better efficiency in ameliorating the toxic effects of lead and increasing the macro nutrients uptake by plants. Lime and eggshell ameliorated Pb uptake of kalmi in shoot (edible parts) by 32.26 and 61.79% compared with the control and reduced root to shoot transfer (TrF) of Pb by15.15 and 30.30% in shoots and roots of kalmi compared to the untreated pots.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 85-92